Economic Policy Uncertainty, Energy Consumption, Trade Openness and CO2 emissions: evidence from BRICS Countries - Selmey, Mousa Gowfal Selmey Gowfal; Elkhodary, Yasmeen Fakery Yaseen; Elsayed, Elsayed Farrag Elsaid Mohamed (International Journal of Energy Economics and Policy, 2024)
This paper investigated the impact of economic policy uncertainty, energy consumption, and trade openness on CO2 emissions in the BRICS countries (Brazil, Russia, India, China, and South Africa) from 1991 to 2023. According to the Panel Pooled Mean Group-Autoregressive Distributed Lag Model (PMG-ARDL), economic policy uncertainty has a significant and negative impact on carbon emissions in the long run, while it has an insignificant effect in the short run. Additionally, primary energy consumption has a significant and positive impact on carbon emissions in the short and long run. Economic growth and trade openness have a positive and significant impact on carbon emissions in the long run. The panel causality test by Dumitrescu and Hurlin (2012) indicated a bidirectional relationship between CO2 and energy consumption, trade openness, and CO2, but a unidirectional causality from CO2 to economic policy uncertainty and economic growth. The study proposes making critical changes in energy policies while accounting for economic policy uncertainty; examining the various types of uncertainty and their effects to develop a climate policy based on evidence and facts and focusing on the discovery of alternative sources of clean energy.